2011
DOI: 10.1016/j.trstmh.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of children hospitalized with dengue fever in an outbreak in Rio de Janeiro, Brazil

Abstract: During a dengue epidemic in Rio de Janeiro in 2007-2008 the Instituto de Puericultura e Pediatria Martagão Gesteira Hospital was a reference for admitted children. The World Health Organization (WHO) considered several manifestations as warning signs of severe dengue This is a retrospective cohort study of all children admitted with dengue fever. Clinical variables considered warning signs by WHO were evaluated in the multivariate analysis, to investigate if they were independently associated with severe dengu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 3 publications
2
14
0
4
Order By: Relevance
“…Sixteen articles published between 2000 and 2012 were ultimately included in this meta-analysis based on the inclusion and exclusion criteria (Figure 1). The final collection consists of 10 prospective [9–11, 17–23], four retrospective [7, 8, 24, 25], and two cross-sectional studies [26, 27]. As listed in Table 1, eight of the 16 studies reported on a population study of children, two on adults and six on both.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen articles published between 2000 and 2012 were ultimately included in this meta-analysis based on the inclusion and exclusion criteria (Figure 1). The final collection consists of 10 prospective [9–11, 17–23], four retrospective [7, 8, 24, 25], and two cross-sectional studies [26, 27]. As listed in Table 1, eight of the 16 studies reported on a population study of children, two on adults and six on both.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Khan et al found that male DF patients were more likely to progress into DHF (OR: 2.3, 95% CI: 1.1–4.5, P value 0.021) [6], while there was no association with SDD [7, 8]. The frequencies of symptoms/signs of vomiting/nausea, abdominal pain, skin rashes, and bleeding were also found to be correlated with SDD [611].…”
Section: Introductionmentioning
confidence: 99%
“…They estimated that 43.9% of the mild dengue cases could have been prevented from hospitalization in 2004. The authors followed up this study with a [150,152] 78.0|22.0% †…”
Section: Disease Prognosticationmentioning
confidence: 99%
“…8,9 The severity of dengue is strongly relating to the presence of abdominal pain. 10 In a recent article from India, it was reported as being seen in up to 70% of the paediatric cases. 8 Conclusively, acute abdomen can be a first presentation of dengue and conservative management can be used similar to general dengue cases.…”
mentioning
confidence: 98%